Annotated Checklist of the Land Snails of Maryland and The District of Columbia - F. Wayne Grimm (Hello World!, 1971)
Although it is a small state which contains only twenty- three counties, Maryland has a fairly rich land snail fauna which has never been surveyed. Scattered collecting has been done by previous workers in all of the state's physiographic provinces, but most collectors simply pass through Maryland enroute to richer collecting grounds in other states. Between 1954 and 1969 I collected extensively throughout the state in order to gather sufficient material for a faunal survey.